Effectiveness of Extension Based on Irene,s Donut Android Version Application on Dental and Mouth Health Status - Yufen Widodo; Abu Hamid (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
Dental health problems often found in children are dental caries. Poor dental health status such as caries that is not treated will cause the child's quality of life to decline. Dental health education aims to tackle dental health problems, the community groups are given motivation in how to maintain dental health. Irene’s Donut application is a caries risk simulator (SRK) of the Inter Active program, which is a communication tool between health workers and parents of students, so that dental health education to parents or students is more interesting and effective. This type of research is quasi-experimental or quasi-experimental, with One Group Pre-Test Post-Design Test design. The population and sample in this study were kindergarten students in the Ilir Barat I Region of Palembang City. Data obtained using the T test method, used normally distributed data. The results showed there were differences between the dental and oral health status of children before and after counseling with the Android version of Irene’s Donut. The statistical tets result showed a significant Based on Irene’s Donut application, the Android version is effective in reducing plaque in children in kindergarten, Ilir Barat I District, Palembang